Ágora de los residuos para la bio-producción plástica (2020)
Based on the analysis of the central Savannah region, a series of social and economic environmental problems are found in the department of Cundinamarca, for which reason it is intervened through a master plan based on connectivity, protection, conservation and economic development. Through an analysis and inventory we are located in the department of Sopo, for the development of a partial plan that contributes to the urban, economic, social and cultural development of the municipality. Action units linked to the current operation of the municipality are generated, taking as an architectural project development, located in the industrial agro-nucleus, which seeks to strengthen the reuse of dairy waste and in the same way contribute to the environmental impact they generate.